The Implementation of CORE Type Cooperative Learning Model to Improve Students Learning Outcome on Integrated Science Module in Junior High School of Pos Keadilan Peduli Umat (PKPU) - Kasli, Elisa; Yusrizal, Yusrizal; Lestari, Windi (Universitas Syiah Kuala, 2020)
The study aims to identify students learning outcome, teachers skills in managing class, along with students response towards the implementation of CORE type cooperative learning model. The study employed Action Research using a descriptive statistical approach. The study was conducted through 4 stages: planning, acting, developing, and reflecting. The participants were 30 second-year Junior High School students of PKPU, and the data were elicited through the scores of students learning outcomes, observation sheet of teachers skills in managing class, and students response sheets toward CORE type cooperative learning model. The finding indicated that students learning outcomes improve from cycle 1 to cycle 3: in cycle 1, the individual completeness is 37% and the classical completeness is 40%; in cycle 2, the individual completeness is 63% and the classical completeness is 70%; in cycle 3, the individual completeness is 93% and the classical completeness is 90%. Moreover, teachers skills in managing the class improve from moderate to a very good category, along with positive responses indicated by the students, where all students show positive responses towards the implementation of CORE type cooperative learning model. It is concluded that the model can significantly improve the students learning outcome on integrated science module